A decade of seascape genetics: Contributions to basic and applied marine connectivity - Selkoe KA; D'Aloia CC; Crandall ED; Iacchei M; Liggins L; Puritz JB; Von Der Heyden S; Toonen RJ (Massey University)
Seascape genetics, a term coined in 2006, is a fast growing area of population genetics that draws on ecology, oceanography and geography to address challenges in basic understanding of marine connectivity and applications to management. We provide an accessible overview of the latest developments in seascape genetics that merge exciting new ideas from the field of marine population connectivity with statistical and technical advances in population genetics. After summarizing the historical context leading to the emergence of seascape genetics, we detail questions and methodological approaches that are evolving the discipline, highlight applications to conservation and management, and conclude with a summary of the field's transition to seascape genomics. From 100 seascape genetic studies, we assess trends in taxonomic and geographic coverage, sampling and statistical design, and dominant seascape drivers. Notably, temperature, oceanography and geography show equal prevalence of influence on spatial genetic patterns, and tests of over 20 other seascape factors suggest that a variety of forces impact connectivity at distinct spatio-temporal scales. A new level of rigor in statistical analysis is critical for disentangling multiple drivers and spurious effects. Coupled with GIS data and genomic scale sequencing methods, this rigor is taking seascape genetics beyond an initial focus on identifying correlations to hypothesis-driven insights into patterns and processes of population connectivity and adaptation. The latest studies are illuminating differences between demographic, functional and neutral genetic connectivity, and informing applications to marine reserve design, fisheries science and strategies to assess resilience to climate change and other anthropogenic impacts.
Keywords: Seascape genetics; Genomics; Connectivity; Marine population genetics; Gene flow; Dispersal; Landscape genetics; 0405 Oceanography; 0602 Ecology; 0608 Zoology